Peningkatan Motivasi Belajar Siswa Kelas X TSM (Teknik Sepeda Motor) Melalui Media Audio Visual Pada Mata Pelajaran PAI di SMK N 1 Batipuh - Abdul Istiqlal, Muhammad (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Student learning motivation plays a crucial role in enhancing enthusiasm, passion, and enjoyment in the learning process. One effort to increase learning motivation is through the utilization of audio-visual media. This media can present lessons in an engaging way, thereby increasing students' interest and enthusiasm for learning. This study aims to examine the improvement of students' motivation in Islamic Religious Education (PAI) by implementing audio-visual media in Grade X at SMKN 1 Batipuh during the 2024/2025 academic year. The research employed a classroom action research method comprising four stages: planning, action, observation, and reflection. Data were collected through observation and questionnaires, then analyzed quantitatively based on the average score of motivation questionnaires. The results indicated an increase in students' learning motivation, from an average score of 45.9% in Cycle I to 75.5% in Cycle II. Thus, the use of audio-visual media is proven to be effective in enhancing students' learning motivation.